Orthodontic treatment of transposition of bilateral maxillary canine and 1st premolar by maintaining the transposed position: A case report - Mahajan, Monika (Journal of Orofacial Research, 2019)
Bilateral tooth transposition between maxillary canine and 1st premolar is a rare finding and poses a challenge to any orthodontist to treat. In definitive treatment plan, one of the treatment alternatives can be finishing the case with alignment of involved teeth in their transposed position whereas the other option is to correct the transposition orthodontically and establishing the natural tooth order. Here a case is presented where transposed positions were maintained with the philosophy to treat by minimizing the negative factors.